Study on The Anti-Inflammatory Effects of Callicarpa nudiflora Based on The Spectrum–Effect Relationship - Li, Yamei; Yang, Yifang; Kang, Xingdong; Li, Xiaofeng; Wu, Yongzhong; Xiao, Junping; Ye, Yang; Yang, Jianqiong; Yang, Yang; Liu, Hai (Frontiers in Pharmacology, 2022)
Callicarpa nudiflora (C. nudiflora) is widely used to treat inflammation-related diseases in China. C. nudiflora mainly contains phenylethanol glycosides, flavonoids, triterpenes, diterpenes, iridoid glycosides, volatile oils, and other small molecules. Therefore, it is necessary to screen out anti-inflammatory active substances from C. nudiflora. In this paper, high-performance liquid chromatography was used to establish the fingerprint of C. nudiflora extracts. The anti-inflammation of C. nudiflora extracts were evaluated by the experiment of toes swelling in inflammatory rats. Then, the spectrum–effect relationship between the fingerprints and anti-inflammatory activities was researched by Pearson analysis and orthogonal partial least squares analysis to identify a group of anti-inflammatory compounds of C. nudiflora extracts. The differences of extracts are illustrated by principal component analysis and cluster analysis in pharmacological effects. Finally, 12 compounds, including catalpol (P1), caffeic acid (P2), protocatechuic acid (P9), 3,4-dihydroxybenzaldehyde (P10), forsythiaside E (P12), protocatechualdehyde isomers (P14), forsythiaside B (P15), rutin (P16), alyssonoside (P21), verbascoside (P22), 2′-acetyl forsythoside B (P24), and isorhamnetin (P32) by HPLC-DAD and UPLC-Q-TOF MS/MS, were determined as potential compounds for anti-inflammatory activity in C. nudiflora. In particular, six compounds were identified as active substances with the greatest anti-inflammatory potential. Moreover, all compounds were tested for anti-inflammatory experiments or anti-inflammatory literature retrieval. In this study, a method for rapid screening of potential anti-inflammatory active ingredients of C. nudiflora was established, which can provide a reference for the future study of active compounds of C. nudiflora.